The Gold Earring: New York City on April 3, 2020, between 2:05 and 2:07 pm - Marcuse, Lara; Fields, Madeline (Ars Medica, 2023)
We (Madeline C. Fields and Lara V. Marcuse) are neurologists in New York City who were deployed to take care of Covid patients during the NYC surge in the Spring of 2020. As the mortality was so high that Spring, we felt surrounded by death and wrote this work of fiction with the voice of someone on the other side of the divide.